Peutz-Jeghers Syndrome: A Case Report and Literature Review in Indonesia - Renaldi, Kaka; Friatna, Yudha (The Indonesian Society for Digestive Endoscopy, 2024)
Background: Peutz-Jeghers Syndrome (PJS) is a rare hereditary polyposis syndrome that is autosomal dominant and has the main characteristics of hamartoma polyps, mucocutaneous pigmentation, and increased susceptibility to malignancy. Case: This case report presented a 19-year-old man referred from a secondary hospital with complaints of diarrhea for one month before hospital administration. The symptoms happened five times a day with residue in the stool. Mucus or bleeding was not found. Around ten days prior, the polyp came out from the anus, but the patient could pull it back by himself. Diarrhea had been recurring since 2014. The patient then underwent polypectomy (while still children) and until now has undergone polypectomy 11 times. Abdominal CT scan showed multiple polyps with varying morphology in the luminal mucosa of the duodenum, jejunum, ileum, descending colon, sigmoid colon, and rectum, in accordance with the presentation of Peutz-Jeghers syndrome. The colonoscopy examination found a Peutz-Jeghers appearance after a polypectomy with a hemoclip installed. The patient was diagnosed with Peutz-Jeghers Syndrome post polypectomy. The patient received a plan for post-operative complete blood count examinations and periodic colonoscopies. Conclusion: PJS is an important diagnosis to consider in young patient with polyposis, even without mucocutaneous pigmentation.